THE INFLUENCE OF WORK CULTURE TOWARD SELF CONTROL (LOCUS OF CONTROL) OF CERTIFIED PRIMARY SCHOOL TEACHERS - Sumardi; Isjoni; Isjoni, M. Yogi Riyantama (International Journal of Educational Best Practices, 2022)
The objective of the study was to analyse how positive and significant the influence of work culture toward self-control (locus of control) of certified teachers at primary schools. The population of this research were 155 certified teachers at primary school in Kuantan Tengah District. Seventy-five certified teachers were randomly selected as samples. The research was undertaken using a correlational research survey design. Data were collected using questionnaires statistically analysed to see if there were any effects on the work culture and teachers’ self-control. This study indicated a significant and positive effect of work culture on primary teachers’ self-control (locus of control). The finding implies that the increase in self-control (locus of control) is possible to achieve by strengthening the work culture.